2001
DOI: 10.1063/1.1367875
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of optical transitions in AlGaAs

Abstract: AlGaAs structures with different aluminum concentration (xϭ0.0, 0.17, 0.30, and 0.40͒ were characterized by photoluminescence and photoreflectance techniques. The temperature dependence of optical transitions in the temperature ranging from 2 to 300 K were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 30 publications
2
37
0
1
Order By: Relevance
“…72 624͒, as evidenced by a rapid linear redshift of the PL peak energies. 27,28 Polimeni et al 15 observed similar S-shaped PL peak energy behavior in the InGaNAs/GaAs QWs, which was interpreted as arising from the detrapping of strongly localized excitons, and subsequent motion of the excitons in weakly localized states, that lie relatively close to the band edge. The temperature at which this detrapping occurred was found to increase with the N concentration of the QW, indicating that the number and/or potential depth of the carrier trapping centers increase with increasing N concentration.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…72 624͒, as evidenced by a rapid linear redshift of the PL peak energies. 27,28 Polimeni et al 15 observed similar S-shaped PL peak energy behavior in the InGaNAs/GaAs QWs, which was interpreted as arising from the detrapping of strongly localized excitons, and subsequent motion of the excitons in weakly localized states, that lie relatively close to the band edge. The temperature at which this detrapping occurred was found to increase with the N concentration of the QW, indicating that the number and/or potential depth of the carrier trapping centers increase with increasing N concentration.…”
Section: Resultsmentioning
confidence: 77%
“…In the 40-100 K interval, a competition between the blueshift associated with the recombination of localized excitons and the regular redshift of the band-gap energy induced by the lattice thermal expansion and the temperature dependence of the electron-phonon interaction takes place. 27,28 These latter phenomena dominate the band-gap dependence at temperatures over 120 K ͑No. 72 637͒ and 150 K ͑No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent work [29] pointed out that the Viña et al [25] and the Pässler [9] models are the most suitable ones to fit the temperature dependence either of the band-gap energy or of the excitonic transition energy. The Viña approach is defined by the expression:…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…O Al x Ga 1-x As possui um "gap" de energia maior que o GaAs e a estrutura criada forma uma região de confinamento bidimensional para os portadores de cargas, com níveis de energia discretos e característicos desse poço em particular. Alterando-se a concentração de Al nas camadas de Al x Ga 1-x As, modifica-se o "gap" de energia do material, sendo possível, inclusive, controlar os níveis de energia dos elétrons e dos buracos no poço quântico (LOURENÇO et al, 2001a(LOURENÇO et al, , 2001b. A figura 1 apresenta uma estrutura de PQS, o perfil do potencial criado pela mesma e a representação da função de onda eletrônica para o estado fundamental em um PQS finito.…”
Section: Poço Quântico Simplesunclassified